STRATEGI PEMENUHAN KEBUTUHAN HIDUP PENYANDANG TUNADAKSA (STUDI KASUS DI DESA PALADINGANG KECAMATAN BONTOLEMPANGAN KABUPATEN GOWA) (Fakultas Dakwah dan Komunikasi, 2020)
This study aims to determine strategies for fulfilling the life needs of people with physical disabilities in the skills aspect (case study in Paladingang Village, Bontolempangan District, Gowa Regency), as well as supporting and inhibiting factors for fulfilling the life needs of people with physical disabilities in the skills aspect (case study in Paladingang Village, Bontolempangan District, Gowa Regency ). This research is qualitative research using a social work approach. The results of this study indicate that the strategies to fulfill the life needs of persons with physical disabilities are making chicken cages from woven bamboo, making wooden knife handles, assembling wooden toy cars, making broomsticks. Then the inhibiting factor is the lack of knowledge about technology, lack of government support and supporting factors, namely the raw materials are easy to obtain, the tools used are simple, the only craftsmen in Paladingang Village. 1) It is hoped that the people in Paladingang Village will always use handicraft products in the village from the skilled hands of people with physical disabilities. 2) For the local government to always provide support to people with disabilities, in the form of support in terms of providing skills guidance to people with physical disabilities, so that these disabled people can develop their skills even better.